Evaluation of Long‐Term Combination Therapy With Peritoneal Dialysis and Hemodialysis. Issue 2 (10th February 2017) - Kanda, Reo; Io, Hiroaki; Nakata, Junichiro; Makita, Yuko; Sasaki, Yu; Matsumoto, Mayumi; Wakabayashi, Keiichi; Tomino, Yasuhiko; Suzuki, Yusuke
Abstract: It is well known that a combination therapy with peritoneal dialysis (PD) and hemodialysis (HD) is feasible and may improve clinical status in patients for whom adequate solute and fluid removal is difficult to achieve with PD alone. The objective of the present study was to evaluate whether the therapy is useful in the likelihood of long‐term peritoneal membrane and cardiac function. The therapy was 6 days of PD and one session of HD per week. Physical, biochemical, dialysate‐to‐plasma ratio of creatinine (D/P Cr), arteriovenous fistula (AVF) blood flow, and left ventricular mass index (LVMI) data were prospectively analyzed in 30 patients with measurements performed at 0 and 6 months, and for 21 patients, 12 or 18 months after initiation of the therapy. The levels of hemoglobin (Hb) after therapy were significantly higher than those at the initiation of therapy. The levels of LVMI and human atrial natriuretic peptide (hANP) after therapy were significantly lower than those at the initiation of therapy, whereas AVF blood flow did not change significantly. D/P Cr levels at 6 months after the therapy were significantly lower than those at the initiation of therapy. D/P Cr levels at 12 or 18 months after the therapy were not aggravated. It appears that the therapy improves Hb levels and cardiac function because of adjusting body fluid status. It was indicated that peritoneal function after therapy may be improved. Therefore, combination therapy is useful from the lifestyle viewpoint of patients in the transition period of PD to HD with end‐stage kidney disease.